Climate and anthropogenic factors determine site occupancy in Scotland's Northern-range badger population: implications of context-dependent responses under environmental change - Silva, A; Curveira-Santos, G; Kilshaw, K; Newman, C; Macdonald, D; Simões, L; Rosalino, L (John Wiley & Sons Ltd, 2017)
Aim: In the light of human-induced rapid environmental change (HIREC), populations are exposed to ever-greater bioclimatic stress at the edge of a species’ historic range. The distribution dynamics of European badgers (Meles meles) at their southern edge are linked tightly to climatic variability. We contribute critical data on how climatic context and local factors determine site occupancy in a northern-range population. Location: Eleven study areas (averaging ~21.3 km 2 ) spread over ~50,000 km 2 in Northern Scotland. Methods: While accounting for heterogeneous detectability, we applied single-season occupancy models to broad-scale camera-trapping data (168 stations) to evaluate how Autumn–Winter weather conditions interact with land-cover type (including agricultural land) and human disturbance to determine badger occupancy. Results: Mean minimum daily winter temperature and elevation influenced inter-site occupancy. When clustering study areas into two distinct topo-climatic types, badger occupancy was associated with agriculture in areas with lower mean minimum winter temperatures ( < 0.3°C) at higher elevation ( > 246 m). In areas with higher mean minimum winter temperature ( > 1.2°C) at lower elevation ( < 133 m), badgers selected sites further away from human infrastructures (settlements and main roads). Climatic factors and human disturbance interact in intricate, context-dependent patterns to determine badger site occupancy. Main Conclusions: The UKCP09 Medium Emissions Scenario projects a winter mean minimum temperature increase of between 1 and 3°C (central estimate) for Northern Scotland by the 2050s. Although warmer weather should benefit badger occupancy, this may be counteracted by up to a predicted 5% human population increase in the Scottish highlands, by 2037, which is likely to disturb badgers. We show that even in instances where species’ regional responses to climate change are positive, these effects can be neutralized by other anthropogenic pressures. Our findings add to the growing body of evidence advocating that interactive effects should be taken into account when planning conservation management.